(untitled) (Applied Biological Research, 2016)
Trichoderma species are commonly used as biological control agents against phytopathogenic fungi and some of its strains are able to produce metabolites that enhance plant growth. In current study the elite rice germplasm population was used for the assessment of root pulling strength (RPS). RSP showed positive correlation with root length and other root parameters. On the basis of RSP, 10 lines each with higher root pulling strength (HRPS) and minimum root pulling strength (MRPS) were selected to check the effect of different Trichoderma spp. on root traits by seed biopriming. RPS varied from 21.5 for rice genotype ‘SLO-16’ to 40 for ‘Cross 116’ and ‘Bhata Phool’. Greater RPS reflected dense root system or greater root length/volume. This analysis revealed that the response of Trichoderma spp. varied with different rice cultivars. Roots were analyzed using Epson perfection v700/v750 3.81 version scanner with WinRhizoReg software. All the isolates of IRRI showed positive response on increase in root length. The growth was enhanced in presence of rhizosphere-competent endophytic strains of Trichoderma, and these characteristics were strain-specific and not characteristic for species. These endophytic plant symbionts can be widely used as seed treatment to control diseases and enhance plant growth and yield.